Disarmament, Demobilization and Reintegration (DDR) in Rwanda, 1997-2008: A Desk Exegesis and Agenda for Praxis - Chukwuma, Okoli, Al (International Journal of Emerging Trends in Social Sciences, 2017)
This paper examines the Rwandan experience of Disarmament, Demobilization and Reintegration (DDR) from 1997 to 2008, with a view to x-raying the nature, pattern, principles, and legacies of DDR in that context, in addition to setting agenda for the practice of DDR elsewhere in Africa. By way of a desk exegesis, the paper posits that DDR was significantly successful given the fact that it led to successful demobilisation and reintegration of a large number of ex-combatants who participated in the Rwanda crisis. The paper notes, however that the Rwanda DDR failed to a large extent in disarming and demobilizing many of the ex-armed groups operating in the country and its proximate region. In the light of the limited success of the Rwandan DDR efforts, it is therefore recommended that future DDR programmes in Africa should be holistic and pragmatic enough to address the concerns of DDR within the formal military sector as well as frontiers of militia formations. This entails considering DDR not merely as a Security Sector Reform (SSR), but essentially, an effort at state building in conflict and post-conflict situations.